(untitled) (Dandao Xuebao/Journal of Ballistics, 2023)
In order to analyze the defects in the theory of firing range test,the transfer mode of system error in test statistics was deduced according to the relationship between system error and true firing range value,and the interference terms of systematic errors in test statistics were obtained. The statistical formulas including error disturbances were established. The larger the sample size,the greater the disturbance of system error. When the sample size increases,the test conclusion can turn to rejecting the original hypothesis. The statistical results of sampling of a variety of a sample quantities and a variety of system error ranges were calculated,and the results were compared. The result shows that the greater the sample size is,the stronger the disturbance produced by the system error. The hypothesis testing theory can be used carefully when the sample size is only small. It is necessary to pay attention to the magnitude of system error and the intensity of the interference in the application of hypothesis test.